Collective LGBT Sem Terra: : the rural and the new projects of homoparental families (Simbiótica. Revista Eletrônica, 2023)
This article sought to investigate the life projects of a group of subjects who manifest a dissident gender and/or sexuality and who formed in 2014, within the Moviemento dos Trabalhadores Rurais Sem Terra (MST), the Coletivo LGBT Sem Terra in the State of Minas Gerais. From life history interviews, we tried to think about how these landless LGBT transformed and constituted their life projects in rural areas. Based on the results of the research, it was concluded that the engagement in the LGBT Sem Terra network changed the individual projects of the interlocutors, such as the pretensions of building monogamous homoparental families within the rural universe of Minas Gerais. At the same time, they took on new collective projects in the fight for respect for sexual diversity and gender expression in the settlements and in the MST.